2022
DOI: 10.1111/josi.12529
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of sexual harassment victimization among adolescents: A scoping review

Abstract: Sexual harassment (SH) is an important public health problem among adolescents and is associated with negative outcomes. Using a theory‐based, developmentally‐informed approach, this scoping review focuses on SH victimization among adolescents (number of studies included = 20) and aims to (1) examine how the extant literature on correlates of SH defined and measured SH, and (2) identify correlates associated with SH victimization among adolescents, focusing particularly on differences between boys and girls. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Across the published papers, these groups comprise non‐Western, ethnic minority, sexual minority, and male victims of sexual harassment. In line with theoretical propositions, for example, social hierarchy theory (see Bolduc et al., 2022), minority groups may be extra vulnerable to sexual harassment due to their lower status in society. From this point of view, sexual harassment may thus be used by perpetrators to reinforce this already lower social position.…”
Section: Cross‐cutting Themesmentioning
confidence: 69%
See 4 more Smart Citations
“…Across the published papers, these groups comprise non‐Western, ethnic minority, sexual minority, and male victims of sexual harassment. In line with theoretical propositions, for example, social hierarchy theory (see Bolduc et al., 2022), minority groups may be extra vulnerable to sexual harassment due to their lower status in society. From this point of view, sexual harassment may thus be used by perpetrators to reinforce this already lower social position.…”
Section: Cross‐cutting Themesmentioning
confidence: 69%
“…Norms and attitudes were also found at the micro‐level, related to young people's close contexts of peers, teachers, and schools. Several of the studies showed that peers convey powerful norms that may influence young people's experiences of sexual harassment and potentially normalize sexual harassment among peers at this age (Bolduc et al., 2022; Honkatukia et al., 2022; Ringrose & Regehr, 2023). Importantly, peer norms were often stereotypically gendered, putting pressure on young men/boys to engage in sexual harassment to appear masculine, and putting shame and blame on girls for being sexually harassed (Ringrose & Regehr, 2023).…”
Section: Cross‐cutting Themesmentioning
confidence: 99%
See 3 more Smart Citations